Science and policy work together to advance food security in Lao PDR - Inphonephong, Souphalack (International Water Management Institute, 2025)
Lao PDR’s national Policy Think Tank partners with IWMI to strengthen officers’ research skills, empowering them to design agricultural policies that are rooted in science and evidence.